A Comparative Study of The Structural-Semantic Peculiarities of English and Uzbek Phrases - Nazarov Sardor Shamurodovich (Western European Studies, 2023)
This article presents a comprehensive comparative analysis of the structural and semantic features inherent in English and Uzbek phrases. Language structures, being the backbone of communication, exhibit unique patterns and nuances across different linguistic landscapes. Through a systematic examination of the phraseological aspects of English and Uzbek, this study aims to unravel the underlying similarities and disparities that contribute to the distinct character of these languages. By employing a combination of linguistic and computational methods, the research explores how cultural, historical, and linguistic factors shape the structural-semiotic landscape of phrases in both languages. The findings shed light on the rich tapestry of linguistic diversity and provide valuable insights into cross-cultural communication
Keywords: Structural Semantics; Phraseology; Cross-Cultural Communication